Bone Morphogenetic Protein 7 Increased Vascular Endothelial Growth Factor (VEGF)-A Expression in Human Granulosa Cells and VEGF Receptor Expression in Endothelial Cells. (April 2014) - Akiyama, Ikumi; Yoshino, Osamu; Osuga, Yutaka; Shi, Jia; Harada, Miyuki; Koga, Kaori; Hirota, Yasushi; Hirata, Tetsuya; Fujii, Tomoyuki; Saito, Shigeru; Kozuma, Shiro
The formation of an individual capillary network in the theca cell layer is required for ovarian folliculogenesis. Although vascular endothelial growth factor (VEGF) is critical for this process, the regulation of VEGF has been unclear. In the present study, the relationship between VEGF and intraovarian cytokine, bone morphogenetic protein 7 (BMP-7) was investigated. Granulosa cells (GC), obtained from in vitro fertilization patients, were cultured with BMP-7 followed by RNA extraction. Human umbilical vein endothelial cells (HUVECs) were also cultured with BMP-7 followed by RNA extraction, tube formation assay, or cell count analysis. The BMP-7 stimulated VEGF messenger RNA (mRNA) and protein expression in GC significantly. In HUVEC, BMP-7 increased an approximately 1.8-fold in the cell number and induced the tube formation significantly compared to control. The BMP-7 also induced a 2-fold increase in VEGF receptor mRNA transcript relative abundance in HUVEC. The BMP-7, a theca cell-derived factor, may stimulate endothelial cell to form vasculature in the follicle via 2 distinct mechanisms, induction of VEGF expression in GC and increased sensitivity of endothelial cells to VEGF.